Precision medicine validation: identifying the MYBPC3 A31P variant with whole-genome sequencing in two Maine Coon cats with hypertrophic cardiomyopathy. Issue 12 (December 2019) - Ontiveros, Eric S; Ueda, Yu; Harris, Samantha P; Stern, Joshua A
Objectives: The objective of this study was to perform a proof-of-concept experiment that validates a precision medicine approach to identify variants associated with hypertrophic cardiomyopathy (HCM). We hypothesized that whole-genome sequencing would identify variant(s) associated with HCM in two affected Maine Coon/Maine Coon cross cats when compared with 79 controls of various breeds. Methods: Two affected and two control Maine Coon/Maine Coon cross cats had whole-genome sequencing performed at approximately × 30 coverage. Variants were called in these four cats and 77 cats of various breeds as part of the 99 Lives Cat Genome Sequencing Initiative (http://felinegenetics.missouri.edu/99lives ) using Platypus v0.7.9.1, annotated with dbSNP ID, and variants' effect predicted by SnpEff. Strict filtering criteria (alternate allele frequency >49%) were applied to identify homozygous-alternate or heterozygous variants in the two HCM-affected samples when compared with 79 controls of various breeds. Results: A total of four variants were identified in the two Maine Coon/Maine Coon cross cats with HCM when compared with 79 controls after strict filtering. Three of the variants identified in genes MFSD 12, BTN1A1 and SLITRK 5 did not segregate with disease in a separate cohort of seven HCM-affected and five control Maine Coon/Maine Coon cross cats. The remaining variant MYBPC 3 segregated with disease status. Furthermore, this gene was previously associated with heart disease and encodes for a protein with sarcomeric function. Conclusions and relevance: This proof-of-concept experiment identified the previously reported MYBPC 3 A31P Maine Coon variant in two HCM-affected cases. This result validates and highlights the power of whole-genome sequencing for feline precision medicine.